High slew rate pulsed electromagnetic field enhances bone consolidation and shortens daily treatment duration in distraction osteogenesis. Issue 12 (8th December 2021) - Li, Yucong; Yang, Yongkang; Wang, Ming; Zhang, Xiaoting; Bai, Shanshan; Lu, Xuan; Li, Yuan; Waldorff, Erik I.; Zhang, Nianli; Lee, Wayne Yuk-Wai; Li, Gang
Abstract : Aims: Distraction osteogenesis (DO) is a useful orthopaedic procedure employed to lengthen and reshape bones by stimulating bone formation through controlled slow stretching force. Despite its promising applications, difficulties are still encountered. Our previous study demonstrated that pulsed electromagnetic field (PEMF) treatment significantly enhances bone mineralization and neovascularization, suggesting its potential application. The current study compared a new, high slew rate (HSR) PEMF signal, with different treatment durations, with the standard Food and Drug Administration (FDA)-approved signal, to determine if HSR PEMF is a better alternative for bone formation augmentation. Methods: The effects of a HSR PEMF signal with three daily treatment durations (0.5, one, and three hours/day) were investigated in an established rat DO model with comparison of an FDA-approved classic signal (three hrs/day). PEMF treatments were applied to the rats daily for 35 days, starting from the distraction phase until termination. Radiography, micro-CT (μCT), biomechanical tests, and histological examinations were employed to evaluate the quality of bone formation. Results: All rats tolerated the treatment well and no obvious adverse effects were found. By comparison, the HSR signal (three hrs/day) treatment group achieved the best healing outcome, in that endochondral ossification and bone consolidation were enhanced. In addition, HSR signal treatment (one one hr/day) had similar effects to treatment using the classic signal (three three hrs/day), indicating that treatment duration could be significantly shortened with the HSR signal. Conclusion: HSR signal may significantly enhance bone formation and shorten daily treatment duration in DO, making it a potential candidate for a new clinical protocol for patients undergoing DO treatments. Cite this article: Bone Joint Res  2021;10(12):767–779.